Joseph Addison an intellectual biography - Poston, Dan 1981- (University of Virginia Press, 2023)
"This book utilizes performance studies and a historicist approach to situate Addison within his intellectual moment and recuperate our understanding of why he was such an important Enlightenment figure"--